A Comparison of Culture Characteristics between Human Amniotic Mesenchymal Stem Cells and Dental Stem Cells - Nurul Hidayat Binti Yusoff,; Saaid Ayesh Alshehadat,; Ahmad Azlina,; Thirumulu Ponnuraj Kannan,; Suzina Sheikh Abdul Hamid, (Tropical Life Sciences Research, 2015)
In the past decade, the field of stem cell biology is of major interest among researchers due to its broad therapeutic potential. Stem cells are a class of undifferentiated cells that are able to differentiate into specialised cell types. Stem cells can be classified into two main types: adult stem cells (adult tissues) and embryonic stem cells (embryos formed during the blastocyst phase of embryological development). This review will discuss two types of adult mesenchymal stem cells, dental stem cells and amniotic stem cells, with respect to their differentiation lineages, passage numbers and animal model studies. Amniotic stem cells have a greater number of differentiation lineages than dental stem cells. On the contrary, dental stem cells showed the highest number of passages compared to amniotic stem cells. For tissue regeneration based on animal studies, amniotic stem cells showed the shortest time to regenerate in comparison with dental stem cells. Semenjak sedekad yang lalu, bidang biologi sel stem menjadi tarikan utama dalam kalangan penyelidik kerana potensi terapeutiknya yang luas. Sel stem adalah satu kelas sel tak terbeza yang berupaya membeza kepada sel jenis khusus. Sel stem boleh dikelaskan kepada dua jenis iaitu sel-sel stem dewasa (tisu dewasa) dan sel-sel stem embrio (embrio yang terbentuk semasa fasa blastosis dalam pembentukan embrio). Artikel ini akan membincangkan mengenai dua jenis sel stem mesenkim dewasa; sel stem gigi dan sel stem amnion dari segi keturunan pembezaan, bilangan pemindahan dan kajian model haiwan. Sel stem amnion mempunyai bilangan keturunan pembezaan yang lebih tinggi berbanding sel stem gigi. Sebaliknya, peringkat bilangan sub-kultur sel stem gigi adalah lebih banyak berbanding sel stem amnion. Untuk pertumbuhan semula tisu, sel stem amnion mengambil masa yang paling singkat bagi penjanaan semula berbanding sel stem gigi, berdasarkan kajian model haiwan.